Tuberous Sclerosis - Gajurel, BP; Acharya, N; Oli, KK; Agrawal, JP (Journal of Institute of Medicine Nepal, 2009)
Tuberous sclerosis is a rare genetic disorder with a variety of clinically remarkable symptoms and signs, of which seizures, mental retardation and facial angiofibromas (Vogt's triad) are considered classical for the diagnosis. Because of the high frequency with which neoplasms are associated with it and because of the involvement of multiple organ systems, all patients with this disease should be evaluated by a multidisciplinary team. The patients should be followed up based on specific guidelines. Key words: multi-system involvement, multidisciplinary approach, tuberous sclerosis. The full text of this paper is available from the Journal of Institute of Medicine website Journal of Institute of Medicine, April, 2009; 31:1 38-41